Spoken communication needs analysis of information desk personnel in libraries / Sujitha Surentharan - Sujitha , Surentharan (2016)
The main aim of this study is to conduct a needs analysis to identify the spoken English language communication needs of the LIDP while catering to the demands and requests of the international students. By identifying their spoken communication needs, their spoken communication skills are identified and incorporated into a proposed English language course design. Dudley-Evans and St. John‟s (1998) framework; Target Situation Analysis (TSA), Present Situation Analysis (PSA) and Learning Situation Analysis (LSA), are used in answering the two research questions. Moreover, a learning-centred course is implemented, as the learners‟ priority in acquiring the language is emphasized. This study is based on a qualitative approach which are supplemented by frequency counts from a set of questionnaire and survey checklist. The questionnaires were completed by 30 LIDP while the survey checklists were completed by 50 international students. Moreover, semi-structured interview sessions were conducted with four LIDP; the Head of the Client Services Division of the Main Library and the Head of the Library of Languages and Linguistics. Additionally, observation sessions were also conducted with four LIDP (whom were interviewed) in further verifying the derived data. Based on the findings , the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication the LIDP’s spoken communication needs are in needs are inneeds are in needs are inneeds are inneeds are inneeds are inneeds are in sufficient practice in pronunciation, inadequate knowledge of vocabulary, insufficient knowledge of grammar and the inability to understand foreign accents. These are the spoken communication skills that are incorporated in the proposed English language course in boosting the LIDP‟s spoken communication competence.